Earth materials : introduction to mineralogy and petrology - Klein, Cornelis (Cambridge University Press, 2017)
"This concise, accessible, market-leading textbook brings together the wide-ranging fundamentals students need to understand rocks and minerals, and shows them how they relate to the broader Earth, materials and environmental sciences. Designed specifically for one-semester courses, it is beautifully illustrated to explain the key concepts in mineralogy and petrology. This edition has been fully updated based on classroom experience, and new features include a completely new chapter providing an elementary introduction to thermodynamics, kinetics, radioactive decay and absolute dating; new mineral descriptions and many new stunning color photographs; and a new section on hydraulic fracturing and discussion of some of its most serious potential environmental consequences. The book uses stunning photos of mineral specimens and rock thin sections to help students build a core understanding. It also creates a highly effective learning experience through close integration of clear illustrations with engaging text, and helps students to easily visualize crystal structures through the CrystalViewer's 3D software, available online"--